Structural characterization of a eukaryotic chaperone: the ribosome-associated complex - Leidig, Christoph; Bange, Gert; Kopp, Jürgen; Amlacher, Stefan; Aravind, Ajay; Wickles, Stephan; Witte, Gregor; Hurt, Ed; Beckmann, Roland; Sinning, Irmgard (Nature structural & molecular biology, 2013)
The eukaryotic ribosome-associated complex (RAC) chaperone is poorly understood. Structural analyses now provide insight into the catalytic inactivity and possible functions of the Ssz1 subunit and reveal that RAC interacts with the ribosome via the Zuo1 subunit. RAC crouches over the ribosomal exit tunnel, where its conformation may be controlled by the ribosomal expansion segment ES27.